Buck Converter based PV Array Emulator for Testing PV Inverters and MPPT Algorithms - Zhongfu Zhou (E3S Web of Conferences, 2024)
This paper presents an emulation of PV modules based on the buck DC/DC converter as a replacement of actual solar electricity generation sources for laboratory experiments for testing the conditioners and MPPT algorithms. The buck converter was designed in constant current control mode and the output current of the buck converter is referred to lookup tables constructed based on I-V curves of product datasheets or mathematical equations. Dynamic performance of the current control loop was investigated. To validate the performance simulation and experiment as carried out and a comparison between simulated and practical results obtained from laboratory test with actual sources is performed. It is confirmed the buck converter-based PV simulator is a simple, safe, versatile, and effective way of physically representing of real solar source.